Education on energy-saving behavior and electrical safety using the demonstration method at RA Al-Istiqomah GSI Serdang - Felycia, Felycia; Lufianawati, Dina Estining Tyas; Nugraha, Adi; Fauzan, Fiqih Dzikri; Pramudya, Galang Dimas (Journal of Community Service in Science and Engineering (JoCSE), 2024)
The energy-saving and electrical safety awareness program at RA Al-Istiqomah GSI Serdang was designed to enhance children's understanding of electrical hazards and promote efficient energy use. The program used the demonstration method with safe electricity educational tools to deliver the material effectively. Children were taught preventive measures against electrical hazards, such as avoiding frayed cables and wet wires and safely using power sockets and electronic devices. Evaluation results showed an average questionnaire score of 4.66 points, which was categorized as very high, supported by interviews confirming participants' increased understanding. Energy-saving practices were presented through demonstrations, videos, and storytelling. This program effectively enhanced children's knowledge and positively impacted the educational environment at RA Al-Istiqomah. Penyuluhan tentang perilaku hemat energi dan keselamatan listrik di RA Al-Istiqomah GSI Serdang bertujuan meningkatkan kesadaran anak-anak terhadap bahaya listrik dan penggunaan energi yang efisien. Kegiatan ini menggunakan metode demonstrasi dengan alat edukasi listrik aman untuk menyampaikan materi secara efektif. Anak-anak diajarkan tindakan pencegahan bahaya listrik, seperti menghindari kabel terkelupas, kabel yang basah, serta penggunaan stop kontak dan perangkat elektronik dengan aman. Evaluasi menunjukkan rata-rata skor kuisioner sebesar 4,66 poin dalam kategori sangat tinggi, didukung oleh wawancara yang mengonfirmasi peningkatan pemahaman peserta. Materi hemat energi disampaikan melalui demonstrasi, video, dan dongeng. Penyuluhan ini terbukti efektif dalam meningkatkan pemahaman anak-anak dan memberikan dampak positif bagi lingkungan pendidikan di RA Al-Istiqomah.